A chimeric influenza virus vaccine expressing fusion protein epitopes induces protection from human metapneumovirus challenge in mice - Chongyu, Tian; Guanglin, Lei; Fang, Sun; Zhuoya, Deng; Hao, Yang; Cong, Li; Xinyu, Li; Wei, He; Lingyun, Tan; Yan, Niu; Penghui, Yang (Frontiers in Microbiology, 2023)
Human metapneumovirus (HMPV) is a common virus associated with acute respiratory distress syndrome in pediatric patients. There are no HMPV vaccines or therapeutics that have been approved for prevention or treatment. In this study, we constructed a novel recombinant influenza virus carrying partial HMPV fusion protein (HMPV-F) , termed rFLU-HMPV/F-NS, utilizing reverse genetics, which contained (HMPV-F) in the the background of NS segments of influenza virus A/PuertoRico/8/34(PR8). The morphological characteristics of rFLU-HMPV/F-NS were consistent with the wild-type flu virus. Additionally, immunofluorescence results showed that fusion proteins in the chimeric rFLU-HMPV/F-NS could work well, and the virus could be stably passaged in SPF chicken embryos. Furthermore, intranasal immunization with rFLU-HMPV/F-NS in BALB/c mice induced robust humoral, mucosal and Th1-type dominant cellular immune responses in vivo. More importantly, we discoveried that rFLU-HMPV/F-NS afforded significant protective efficacy against the wild-type HMPV and influenza viruse challenge, with significantly attenuated pathological changes and reduced viral titers in the lung tissues of immunized mice. Collectively, these findings demonstrated that chimeric recombinant rFLU-HMPV/F-NS as a promising HMPV candidate vaccine has potentials for the development of HMPV vaccine.